Perancangan Sistem Monitoring Kemiringan Bongkar Muat di Kapal Bulkcarrier Menggunakan Sensor Gy-521 Berbasis Lora - Aji Pamungkas; Edi Kurniawan; Faris Nofandi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Ship stability problems are one of the causes of ship accidents such as ships that are difficult to control, unbalanced and sinking, either at sea during shipping or during loading and unloading. This is the background for the need to improve ship safety systems to reduce ship accidents. The purpose of this research is to accurately monitor the loading and unloading slope and determine the maximum distance that can be connected to LoRa. The working system of this tool is made with the intention of preventing ship accidents and creating a better sea transportation system. The work process of this tool is done by reading the tilt angle of the ship which will then be read through the LCD screen and the LED lights will light up and the buzzer will sound if it reaches a certain tilt angle. Making it easier for loading and unloading operators to manage their cargo so that the ship remains stable.The methodology and design of the applied scientific work tool system that will be carried out using experimental research methods. Experimental research methods are used to produce certain products, and test their effectiveness. The results of research on this applied scientific work are the accuracy of the gyroscope sensor GY-521 mpu-6050 which is 98.71% with an error of 1.29% and the distance of LoRa Ra-02 SX1278 that can be reached on a stable wireless system is as far as 370m in water and 205m on land. More than that the receiver cannot receive data anymore or is invalid.